Social Inversions and Education - D. A. Sevost'yanov (Moscow Polytechnic University, 2019)
The article focuses on hierarchical and inverse relations in social systems. Hierarchy is the basic form of organization in social systems. Complex hierarchies have the ability to form inverse relationships. Inverse relationships occur when the lower element in social hierarchy becomes the dominant, but formally remains in a subordinate position. In a hierarchical system, there are certain organizational principles that determine the mutual position of the elements. There are several such principles in complex hierarchies. Inversions arise when two or more organizational principles collide in social hierarchy. The developed inversions are a manifestation of internal contradictions in the hierarchical system. The accumulation of these contradictions can lead to the collapse of the hierarchical system. For example, the development of social inversions can cause a revolution in which certain organizational principles in the social system are abolished. But in some cases, resolving of these contradictions leads to another step in the progressive development of the system. Thus, the resolution of contradictions occurs when the subject actually moves to a higher position in the social hierarchy. One of the most important organizational principles that determine the position of the subject in the social hierarchy is based on the educational level of this subject. Increasing the level of education entails the increase of the subject's social status. However, the position of the subject in the social hierarchy is also determined by other organizational principles. These principles may conflict with the educational organizational principle. As a result, there is a social inversion. Education is a factor that can both generate inversions in the social hierarchy and eliminate them. The development of society is closely connected with the manifestations of the educational organizational principle, with its interaction with other organizational principles in the social hierarchy. The analysis of inverse relations in social hierarchies is an effective research tool that allows to predict and prevent social tension in society.